2024
DOI: 10.1007/s00018-023-05098-8
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the NF-κB pathway as a potential regulator of immune checkpoints in cancer immunotherapy

Nasim Ebrahimi,
Al-Hasnawi Rasool Riyadh Abdulwahid,
Atena Mansouri
et al.

Abstract: Advances in cancer immunotherapy over the last decade have led to the development of several agents that affect immune checkpoints. Inhibitory receptors expressed on T cells that negatively regulate the immune response include cytotoxic T‑lymphocyte antigen 4 (CTLA4) and programmed cell death protein 1 (PD1), which have been studied more than similar receptors. Inhibition of these proteins and other immune checkpoints can stimulate the immune system to attack cancer cells, and prevent the tumor from escaping t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 239 publications
0
0
0
Order By: Relevance
“…NFkB is shown to maintain the tumor promoting phenotype of TAM in certain cancers 29 . NFkB has been also linked to evolution of inflammatory tumors 30 . In our study, we found that in TAMs, the NFkB was highly upregulated and after TD treatment, NFkB downregulated significantly ( Figure 4c ).…”
Section: Resultsmentioning
confidence: 99%
“…NFkB is shown to maintain the tumor promoting phenotype of TAM in certain cancers 29 . NFkB has been also linked to evolution of inflammatory tumors 30 . In our study, we found that in TAMs, the NFkB was highly upregulated and after TD treatment, NFkB downregulated significantly ( Figure 4c ).…”
Section: Resultsmentioning
confidence: 99%